(a-3b)^3+(3b-c)^3+(c-a)^3
Answers
Answered by
38
if x+y+z=0
x=a-3b
y=3b-c
z=c-a
a-3b+3b-c+c-a
=0
then x+y+z =3xyz
3(a-3b)(3b-c)(c-a)
x=a-3b
y=3b-c
z=c-a
a-3b+3b-c+c-a
=0
then x+y+z =3xyz
3(a-3b)(3b-c)(c-a)
Answered by
28
HEYA!!
Your answer is it the attachment.....
HOPE IT HELPS!!!!
Your answer is it the attachment.....
HOPE IT HELPS!!!!
Attachments:
![](https://hi-static.z-dn.net/files/d2e/6032c1f8679b0eb19938d5d72d61dfe6.jpg)
Similar questions
French,
8 months ago
Computer Science,
8 months ago
Geography,
8 months ago
History,
1 year ago
Math,
1 year ago